2014
DOI: 10.1111/1471-0528.12513
|View full text |Cite
|
Sign up to set email alerts
|

What do popular Spanish women's magazines say about caesarean section? A 21‐year survey

Abstract: ObjectivesCaesarean section (CS) rates are increasing worldwide and maternal request is cited as one of the main reasons for this trend. Women's preferences for route of delivery are influenced by popular media, including magazines. We assessed the information on CS presented in Spanish women's magazines.DesignSystematic review.SettingWomen's magazines printed from 1989 to 2009 with the largest national distribution.SampleArticles with any information on CS.MethodsArticles were selected, read and abstracted in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 25 publications
5
21
0
Order By: Relevance
“…42,43 These results suggest the need for the improved reporting of information about route of delivery in popular media. It is often justified that the lack of space in printed media is a reason for the incomplete information presented in magazines.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…42,43 These results suggest the need for the improved reporting of information about route of delivery in popular media. It is often justified that the lack of space in printed media is a reason for the incomplete information presented in magazines.…”
Section: Discussionmentioning
confidence: 98%
“…Avoidance of pain and shorter time to delivery were among the most frequently reported advantages of caesarean section on the web, as in previous studies about information on caesarean section in magazines. 42,43 The veracity of online health information is a key issue because consumers are not trained or knowledgeable enough to critically appraise the quality of the information that they receive. The practice of unconditionally accepting online health information can be harmful because a large proportion of patients do not discuss the knowledge acquired from websites with doctors, as they feel confident about the credibility of the information obtained from this source.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reasons for such dramatic increases are multifactorial, including medical as well as non‐medical reasons 3, 6, 7. It has been suggested that non‐medical factors, such as social, cultural, or unequal accessibility to health services, as well as clinical practice patterns/styles, might have been major contributors to the wide variation in caesarean section rates across different countries 1, 2, 6, 7, 8, 9, 10. On the other hand, we can presume that the rates of medically necessary caesarean section associated with the lowest maternal and neonatal mortality should vary less among countries, if the same indications for caesarean section had been applied across all nations 4, 11.…”
Section: Introductionmentioning
confidence: 99%
“…C‐sections lead to higher maternal death rates, more extensive medical intervention, and longer hospital stay and recovery times. Other adverse effects of C‐sections include not being able to move easily for a while, higher risk of complications, delay in mother–baby interaction and lactation, starting oral nutrition after a longer period, and undergoing a surgical operation (Ejder Apay & Pasinlioğlu, ; Torloni, Campos Mansilla, Merialdi, & Betran, ). This is why it is very important to improve comfort levels with effective health care for the mother and the baby after a C‐section.…”
mentioning
confidence: 99%